Compulsory Licensing: An Antidote for the Dissemination of Potential COVID-19 Cure? - Rajesh, Nandini; Kuttan, Arya (Kathmandu School of Law Review, 2020)
This paper extensively examines the role of Compulsory Licensing in the Intellectual Property regime with regard to potential COVID-19 vaccinations. In Parts I and II, the paper analyzes the concept of compulsory licensing along with its need. Part III discusses the usage of the flexibilities laid down by the TRIPS Agreement by developing nations after the adoption of the Doha Declaration. This throws light on the status quo pertaining to its implications and repercussions and further helps in determining the situation upon invoking compulsory licensing in the current pandemic scenario. Parts IV and V discusses the pre-emptive measures taken by nations by means of laying forth foundational steps and the legal procedures involved in legitimizing the issuance of these licenses for potential COVID-19 vaccines. It discusses steps taken by various nations across the world, the reasons for doing so and their current legal status pertaining to the licenses. Part VI discusses in detail the diverging views that exist primarily between the United States of America and European Union. It entails discussions regarding accessibility and affordability of potential COVID-19 vaccines in the wake of a jurisprudential analysis of the existing legal provisions relating to compulsory licenses in both provinces. Further, Part VII lays down the negative implications which may arise while invoking compulsory licenses for potential COVID- 19 vaccines. This gives a detailed view of the need for the public healthcare to undertake a balanced approach of the interests of both, the patentee and the public at large. It also lays down the importance of adequate remuneration for the pharmaceutical companies which is often overlooked. Finally, Part VIII analyses both perspectives and lays down the importance of compulsory licensing with regard to both, accessibility and affordability.